The effect and safety of olanzapine on nausea and vomiting in children receiving moderately emetogenic chemotherapy - Aziz Eghbali; Tahereh Bagherloo; Ali Ghasemi; Roghayeh R Afzal; Aygin Eghbali; Kazem Ghaffari (Advanced Biomedical Research, 2023)
Background: In order to improve the complete recovery of nausea and vomiting, we conducted a study with the aim of preventing acute and delayed nausea and vomiting in children undergoing moderate emetogenic chemotherapy. Materials and Methods: A clinical trial study was done on 130 children received chemotherapy. Patients received olanzapine and placebo. All groups received granisetron along with dexamethasone (DEX). The severity of chemotherapy-induced nausea and vomiting (CINV) induced by chemotherapy was compared in two groups. Results: The severity of nausea on the first, second, third, and fourth days was not significantly different (P > .05) in two groups. The number of patients without vomiting was significantly different during the first 24 hours after chemotherapy between patients in the two groups (82.3% vs 64.5%; P = .016). Conclusion: This study showed that olanzapine, which acts as an inhibitor of neurotransmitters, had a favorable efficacy in controlling acute and delayed CINV. More studies with large sample size are needed to compare the effect of olanzapine with other agents including aprepitant and palonosetron in the prevention of CINV.